1984
DOI: 10.1139/b84-117
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic comparison between progressive and monocarpic senescence of soybean

Abstract: The onset of senescence, defined as the time that photosynthesis began to decline irreversibly, was compared with ribulose-1,5-bisphosphate carboxylase (EC 4.1.1.39) (RuBPCase) activity, chlorophyll content, protein content, and leaf diffusive resistance in outdoor-grown soybean (Glycine max (L.) Merr. cv. Amsoy 71) leaves that had emerged and senesced during different stages of plant ontogeny. The purpose was to compare metabolic events in soybean leaves associated with progressive and monocarpic senescence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…18) and were greater than those reported in other studies of soybean cotyledon photosynthesis (1,4,5,9). Rates reported here were clearly in excess of dark respiration even in young cotyledons that showed high dark respiration rates.…”
Section: A' C-)contrasting
confidence: 70%
See 1 more Smart Citation
“…18) and were greater than those reported in other studies of soybean cotyledon photosynthesis (1,4,5,9). Rates reported here were clearly in excess of dark respiration even in young cotyledons that showed high dark respiration rates.…”
Section: A' C-)contrasting
confidence: 70%
“…The amount of enzyme increased until day 6 and then decreased steadily until decapitation at day 18 (Fig. 2).…”
Section: Rubiscomentioning
confidence: 91%
“…Two types of senescence have been described for soybean under field conditions: progressive senescence of lower leaves before reproductive growth and monocarpic senescence of the remaining leaves during the pod fill phase of reproductive growth (28). Wells (32) showed that the loss of lower canopy leaves was not closely associated with light interception subsequent to canopy closure, an indication that the shaded leaves do not contribute significantly to whole plant photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…First, extreme shade conditions can induce rapid senescence of lower canopy leaves several weeks in advance of monocarpic senescence of the whole plant (Secor et al 1984;Burkey and Wells 1991;Wells 1991). During the development of a closed soybean canopy, many leaves expand under full sun and later function in extreme shade following the development of leaves at higher nodes.…”
Section: Introductionmentioning
confidence: 99%